A Loose-packing Approach for Coil Embolization of Giant Intracranial Aneurysm - Simon C.H. Yu (Asian Journal of Surgery, 2007)
Endoluminal occlusion of giant intracranial aneurysms with coil embolization is a viable endovascular treatment option alternative to surgical clipping. However, due to the relatively large aneurysm size, the use of embolization coils for giant aneurysms could be great. A loose-packing embolization strategy in which the fundus of the aneurysm is loosely packed while the aneurysm base is tightly packed is presented. Such a coiling strategy is best suited to giant aneurysms of elongated configuration and narrow neck as illustrated in the present case. While the use of the loose-packing approach is recommended for elongated aneurysms with a narrow neck, its use is not to be generalized for aneurysms of other configurations.